Gordon syndrome in an 11-year-old boy: long-term follow-up - Badeński, Andrzej; Badeńska, Marta; Bjanid, Omar; Czubilińska-Łada, Justyna; Gliwińska, Aleksandra; Bogdał, Anna; Kupczyk, Olga; Szczepańska, Maria (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Gordon syndrome, or type 2 pseudohypoaldosteronism, is a rare familial occurring hypertension, in most cases inherited in an autosomal dominant manner. It is characterised by coexisting hyperkalaemia, which is not found in other monogenic forms of hypertension. In addition, in this syndrome aldosterone levels are usually low, and renin activity is reduced under normal salt loading. Renal function, assessed on the basis of glomerular filtration rate, is normal, but metabolic acidosis – type IV renal tubular acidosis – may occur. The authors would like to present the case of an 11-year-old boy in whom the above-described symptoms of Gordon syndrome were observed; clinically effective thiazide diuretic therapy, and subsequent genetic analysis confirmed the diagnosis.